FAKTOR YANG MEMPENGARUHI KEJADIAN STUNTING PADA ANAK USIA 2-5 TAHUN DI KEPULAUAN MANDANGIN - Nelyta Oktavianisya; Sri Sumarni; Sugesti Aliftitah (Universitas Islam Negeri Alauddin Makassar, 2021)
Stunting is a linear growth disorders, caused by chronic malnutrion of nutrient intake or chronical nor recurrence infectious diseases, showed by Z-score height according to age less than -2 SD. The aim of this study was to analize factors related to stunting on 2-5 years old children In Pulau Mandangin Kabupaten Sampang. This study was analytic study with case control approach. The population of this study were every mother of children with 2-5 years age who lived in Pulau Mandangin in 2019. Case group were mother of children with 2-5 years ages with stunting diagnosis (76 respondents). Control group were mother of children with 2-5 years ages without stunting diagnosis (152 respondents). Simple random sampling technic was used on sample retrieval and data retrieval using questioner. The data analized by using univariate, bivariate (chi-square) and multivariate analysis with logistic regression test with 5% (α=0,05) level of significance. The study result showed that related variable to stunting were low birth weight baby with p-value 0,015. Genetic history with p-value 0,008, nutrient intake with p-value 0,011, exclusive breast milk with p-value 0,004, and environment with p-value 0,009. The result of multivariate analysis nutrient intake had great risk of stunting (p=0,013 OR=4,0, 95% CI=1,091 –14,821). Nutrient intake is dominant factors related to stunting incident. There was influence of low birth weight status, genetic, exclusive breast milk, nutrient intake and environment. While economic status was not related to stunting incident on children with ages 2-5 years in Pulau Mandangin Kabupaten Sampang.